The Hypertention and Mechanic's Lifestyle in Medan City and Its Relation to Nutritional Status: Kejadian Hipertensi dan Gaya Hidup Mekanik Bengkel di Kota Medan serta Kaitannya dengan Status Gizi - Damanik, Kanaya Yori; Haryana, Nila Reswari; Sandy, Yatty Destani; Permatasari, Tyas (Universitas Airlangga, 2024)
Background: Lifestyle has a role in determining a person's nutritional status, such as eating habits, smoking habits, physical activity, and alcohol consumption. Mechanics tend not to pay special attention to health, especially in their lifestyle. In addition, the majority of mechanics have high blood pressure. Therefore, the authors were concerned about their nutritional status and its relationship with the affecting factors. Objectives: To analyze the correlation of age, lifestyle, and blood pressure with the nutritional status of repair shop mechanics. Methods: This study used a cross-sectional design on 70 mechanics at 12 motorcycle repair shops in 6 districts of Medan City. Age and lifestyle data were obtained from questionnaires, blood pressure data from direct measurements using a sphygmomanometer twice with a five-minute interval, and nutritional status data from anthropometric measurements. All collected data were analyzed using Spearman's Correlation with the Kolmogorov Smirnov's normality test. Results: The bivariate test showed a significant relationship between smoking (p=0.004, r=-0.342), physical activity (p=0.000, r=-0.484), sodium intake (p=0.000, r=0.570), and blood pressure (p=0.001, r=0.382) with the nutritional status of mechanics. Meanwhile, no significant relationship exists between age (p=0.255) and alcohol consumption habits (p=0.774) with mechanical nutritional status. Conclusions: Mechanical nutritional status negatively correlated with smoking and physical activity but positively correlated with sodium intake and blood pressure.